2013
DOI: 10.5539/ijbm.v8n20p96
|View full text |Cite
|
Sign up to set email alerts
|

Base Inventory Cooperation Strategy of Multi-parts with Supply-Hub

Abstract: We investigate two stage supply chain optimization coordination with Supply-Hub operation mode for assembly manufacturing enterprise. Because all parts delivery of all suppliers are integrated at Supply-Hub, all needed parts by the production line are selected, packaged and then sent to the manufacturer by Supply-Hub. We applied queuing theory and basic inventory strategy to model this system and derive the optimization solution for decentralized decision and centralized decision separately. Then coordination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…This gap is notable because innovation is crucial to firm survival and growth (Baumol ). When firms, especially SMEs, lack the internal resources needed to innovate, which implies a situation of dependency, they might adopt either cooperation or integration strategies (Shuang‐yan, De‐Zhi, and Fang‐Ping ; Wang and Zajac ). It seems likely that there is some link between the sources of dependence and the strategic choices to innovate.…”
Section: Sources Of Dependence and Strategies To Innovatementioning
confidence: 99%
See 1 more Smart Citation
“…This gap is notable because innovation is crucial to firm survival and growth (Baumol ). When firms, especially SMEs, lack the internal resources needed to innovate, which implies a situation of dependency, they might adopt either cooperation or integration strategies (Shuang‐yan, De‐Zhi, and Fang‐Ping ; Wang and Zajac ). It seems likely that there is some link between the sources of dependence and the strategic choices to innovate.…”
Section: Sources Of Dependence and Strategies To Innovatementioning
confidence: 99%
“…Some SMEs adopt an integration strategy to innovate and develop a new product, which consists of three general forms: employee training, recruitment, and firm acquisition. An integration strategy allows SMEs to retain and increase control of the activities of the innovation process and offers more protection for the innovation outcomes and high‐value assets (Pisano and Teece ; Shuang‐yan, De‐Zhi, and Fang‐Ping ; Teece ), while also reducing the threat of opportunistic behavior. However, integration is often more expensive than cooperation, despite the reduced transaction costs and increased income (Wang and Zajac ).…”
Section: Sources Of Dependence and Strategies To Innovatementioning
confidence: 99%
“…Shah and Goh (2006) proposed an organized hierarchical model for managing the inventories according to the supply hub so as to aid in achieving the stability between different bodies existing in the supply chain. Several researchers such as Li et al (2008), Li et al (2009) and Shuang-yan et al (2013) showed benefits of using the supply hub. Qiu et al (2014) studied how manufacturers and SHIP can interact so as to optimize their decision on replenishment, delivery and storage pricing.…”
Section: Introductionmentioning
confidence: 99%